Original Research: The Effects of Red Yeast Rice Supplementation on Cholesterol Levels in Adults. Issue 8 (August 2017) - Peng, Diane; Fong, Amy; Pelt, Amanda van
Abstract : N/A: Purpose: Red yeast rice (RYR) supplementation has become a popular alternative to statin therapy in treating hypercholesterolemia. This state-of-the-science review seeks to explore the most recent evidence on the effectiveness and safety of RYR supplementation in treating dyslipidemic adults. Methods: This review extends the time frame of a meta-analysis performed by Li and colleagues in 2014; specifically, we looked at the literature published between September 2013 and April 2016. We conducted a search of four electronic databases—PsycINFO, CINAHL, PubMed, and Scopus—using the terms red yeast rice and cholesterol . We excluded studies that included berberine or lovastatin. Results: Fifteen articles met the inclusion criteria. Eleven articles reported on randomized controlled trials, one reported on an open-label pilot study, and one reported on an open-label clinical trial. Two articles were meta-analyses. The 13 studies involved a total of 1, 246 participants, with an additional 7, 467 participants reported in the two meta-analyses. Significant reductions in low-density lipoprotein cholesterol and total cholesterol levels with RYR supplementation were observed in all trials. There were no significant changes in liver and kidney function, and 10 studies noted no significant changes in creatine kinase levels. Conclusions: Although RYR appears to be a safe and effective lipid-lowering agent, there is insufficient evidence to support the recommendation of RYR supplementation to patients. Further research is needed, including long-term studies, studies that include participants with comorbidities and complex medical histories, and studies that take into account the variability of formulation and dosage of RYR in the marketplace. Abstract : In this state-of-the-science review, the authors explore the most recent evidence on the effectiveness and safety of red yeast rice supplementation, an increasingly popular alternative to statin therapy, in treating hypercholesterolemia in dyslipidemic adults.